ANALISIS PERBANDINGAN PEMBAYARAN PAJAK AIR BAWAH TANAH OLEH PERUSAHAAN DI KABUPATEN LABUHANBATU SELATAN TAHUN 2023 DAN 2024 MENGUNAKAN METODE UJI TANDA - Syavira, Muddini; Intan, Sari; Muliani, Fitra (JURNAL GAMMA-PI, 2025)
This study aims to examine changes in the number of companies paying groundwater tax in Labuhanbatu Selatan Regency in 2023 and 2024. Groundwater tax serves as one of the revenue sources for local governments and supports development as well as water resource management. The data were obtained from the Regional Revenue Agency of Labuhanbatu Selatan and analyzed using a non-parametric statistical method, namely the sign test, to evaluate the paired data from the two periods. The results indicate an increase in the number of companies paying the tax in 2024 compared to 2023. The significance value of 0,006, which is below the 0,05 threshold, confirms that the increase is statistically significant. Therefore, it can be concluded that company compliance with groundwater tax payments improved in 2024. This finding suggests the need for continuous monitoring and guidance from the local government to maintain and strengthen this positive trend.